Reuse of Lithium Batteries: A Comprehensive Study on Opportunities, Regulations, and Perspectives in Germany and Costa Rica - Denz, Emily (2024)
This research project places a strong emphasis on the reuse of lithium-ion batteries as a central element in the transition to carbon neutral energy. The technical, legal and financial aspects of these processes in Germany are described in detail to provide a comprehensive understanding of the reuse and recycling practices of lithium batteries. Special attention is given to the reuse of large batteries, with concrete examples of the situation in Germany. Potentials and challenges related to smaller batteries are also addressed, pointing out that in Germany the reuse of lithium-ion batteries from small devices does not seem to be economically profitable. A significant contribution of this paper is the presentation of the German approach as an inspiring model for developing countries such as Costa Rica. It highlights the possibility of applying these processes on a smaller scale, especially for smaller devices. The idea is that the German approach can serve as a guideline for the sustainable use of lithium-ion batteries in countries that are still in the development phase. In summary, this project contributes to raising awareness of the importance of reusing lithium-ion batteries in the context of the energy transition and presents concrete examples as well as possible applications for developing countries, thus contributing to global sustainability.